INTERPERSONAL COMMUNICATION OF THE SUJANLIE TOTONG LAW OFFICE WITH CLIENTS IN RESOLVING LEGAL PROBLEMS: A CASE STUDY OF THE BUSANG DENGEN FARMER GROUP - Nunung Dwi Astutik; Nurul Shobah; Fuad Fansuri (Jurnal Visi Komunikasi, 2026)
This study aims to analyze the interpersonal communication carried out by the Sujanlie Totong Law Office with clients in resolving legal problems, using a case study of the Busang Dengen Farmer Group. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the advocate and supported by relevant literature review.The findings indicate that interpersonal communication is implemented through the use of simple and accessible language, transparency in conveying information, empathy toward clients, and active client involvement in legal decision-making processes. Such communication plays a crucial role in building client trust, reducing uncertainty, and enhancing clients’ understanding of legal procedures.Furthermore, interpersonal communication functions not only as a means of delivering legal information but also as an instrument of empowerment, enabling clients to actively participate in the process of resolving their legal issues.Therefore, the interpersonal communication practiced by the Sujanlie Totong Law Office is not merely informative in nature but also strategic in supporting the effectiveness of legal problem resolution faced by clients.